2005
DOI: 10.1093/jnci/dji207
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Independent Skin Recruitment and Activation of Plasmacytoid Predendritic Cells Following Imiquimod Treatment

Abstract: Imiquimod induces immune activation patterns that relate to the number of the PDCs recruited to the treatment site, thus supporting the role of PDC in responsiveness to imiquimod in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 53 publications
11
145
0
5
Order By: Relevance
“…Topical application of Aldara, a cream containing 5% of the TLR7-agonist IMQ, is an effective treatment for BCC and AK, and its major mode of action is thought to be TLR7 dependent. Indeed, topical application of Aldara results in increased infiltration of pDCs, a cell type that expresses high levels of TLR7 and is the main producer of type I interferon (IFN) 6 . Furthermore, Aldara induces local psoriasis-like symptoms in susceptible humans and in mice, such as inflammation, thickening and scaling of the skin [20][21][22] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical application of Aldara, a cream containing 5% of the TLR7-agonist IMQ, is an effective treatment for BCC and AK, and its major mode of action is thought to be TLR7 dependent. Indeed, topical application of Aldara results in increased infiltration of pDCs, a cell type that expresses high levels of TLR7 and is the main producer of type I interferon (IFN) 6 . Furthermore, Aldara induces local psoriasis-like symptoms in susceptible humans and in mice, such as inflammation, thickening and scaling of the skin [20][21][22] .…”
Section: Resultsmentioning
confidence: 99%
“…pDCs have been reported as the most prominent cell type infiltrating BCC following Aldara treatment 6 and as crucial for Aldara-dependent anti-tumour effects in murine melanoma 7 . To investigate whether this is also the case in human AK, we stained four AK sections with CD123, a marker for human pDCs.…”
Section: Aldara Induces Keratinocyte Proliferation In Human Nmscmentioning
confidence: 99%
See 1 more Smart Citation
“…The known functions of these mediators explain, at least in part, many cellular responses to imiquimod including activation and application-site-directed migration of dendritic cells and their precursors as well as attraction and stimulation of cytotoxic T-lymphocytes and other immune cells. Along this line, it has been demonstrated that plasmacytoid dendritic cells accumulate in subcutaneous melanoma metastases in a mouse model (Palamara et al, 2004) and that plasmacytoid predendritic cells migrate into the skin (Urosevic et al, 2005) following application of imiquimod. The net result of the imiquimod-induced cytokine production is a Th1-weighted cellular immune response, while Th2 signaling pathways appear to be suppressed.…”
Section: Tlr7 and Tlr8 As Targets In Cancer Therapymentioning
confidence: 98%
“…Oligodeoxynucleotides (ODN) with unmethylated deoxycytidyldeoxyguanosine (CpG) dinucleotides (CpG ODN) mimic the immunostimulatory activity of bacterial DNA recognised by the Toll-like receptor 9 (TLR9) and are potent adjuvants utilised in cancer therapy (Jahrsdorfer et al, 2005). Imiquimod is a TLR-7 agonist extensively used in the treatment of basal cell carcinoma (Urosevic et al, 2005).…”
Section: Tlrs and Anticancer Immunotherapymentioning
confidence: 99%